Hegemonic dynamics and social inequalities in child stunting: An interpretive qualitative study in Indonesia - Sarifudin Andi Latif; Muhammad Syafri; Muhammad Ilyas; Sri Wahyuni; Farida Latif (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Child stunting remains a major public health concern in low- and middle-income countries, reflecting not only nutritional deficiencies but also broader social and structural inequalities. This study aimed to analyze child stunting as a socially constructed phenomenon shaped by hegemonic processes, focusing on how power relations, knowledge systems, and structural constraints contribute to its persistence in a local Indonesian context. Research Methodology: This study employed an interpretive qualitative design within a health sociology framework. Data were collected in Jeneponto Regency, South Sulawesi, Indonesia, between February and March 2026. A total of 18 participants were recruited using purposive and snowball sampling, including mothers of stunted children, healthcare workers, and community leaders. Data collection involved in-depth interviews, participant observation, and document analysis. Thematic analysis was conducted using NVivo software, following iterative coding and theme development procedures. Results: Five major themes emerged: (1) normalization of stunting as a non-pathological condition, (2) dominance of biomedical knowledge alongside partial adherence to local practices, (3) unequal access to nutritional and health resources, (4) top-down implementation of health programs limiting community agency, and (5) reproduction of caregiving practices under structural constraints. Data saturation was achieved at the 16th interview and confirmed with 18 participants. These findings indicate that stunting is maintained through interconnected social, economic, and ideological processes. Conclusion: Child stunting is sustained not only by material deprivation but also by hegemonic processes that normalize inequality and shape health practices. Effective interventions should move beyond technical solutions by incorporating community participation, addressing structural inequities, and integrating local knowledge into health strategies. Such approaches are essential to achieve more equitable and sustainable outcomes.